Effects of Combined Strategy Instruction and Attribution Retraining in Mathematics Achievement of Form One Students in A Secondary School - Loh, Sau Cheong (2002)
Students form beliefs of success and failure towards learning and these have implications on coping with their learning problems. In the process of learning, it is important for them to identify the causes of failure and success in order to achieve higher performance and acquire learning strategies to master their learning. This study examined the effects of combined strategy instruction and attribution retraining (SI + AR) on students' causal attributions, learning strategies and achievement. Causal attributions in this study were based on three dimensions, that is, whether the results were due to the subjects themselves (internal) or others (external), whether the causes were changing in nature (unstable) or unchanging over time and place (stable) and whether the subjects can control (controllable) or cannot control (uncontrollable) the causes concerned. A total of 133 Form One students were randomly chosen from one specific school. They formed four randomised cluster sampling classes. Subjects underwent the testing for eight days and the treatment for twenty days. The Nonequivalent Control Group Design consisting of three experimental groups and one control group was used. The experimental treatments were the SI + AR, the strategy instruction only (SI Only) and the attribution retraining only (AR Only). The control group had no treatment. All tests were administered before and after the treatment.